2014
DOI: 10.1590/s0102-86502014000200003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simvastatin on the regeneration of surgical cavities in the femurs of rabbits

Abstract: PURPOSE:To evaluate the effect of a local application of simvastatin gel in repairing bone defects in the femurs of rabbits. METHODS:Two standard surgical cavities were created in the femoral epiphysis of 18 rabbits. In the simvastatin group (SG), the cavities were filled with a collagen sponge soaked in 0.5 ml of a simvastatin (1 mg) gel, and the cavities were covered with a biological membrane. The bone cavities in the second group (control group) were filled with a blood clot and covered with a biological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In animal studies the influence on mineralization, osteogenic markers and viability of quiet equal concentrations of SV were investigated upon cells particularly of rodent origin [21][22][23][24][25][26][32][33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies the influence on mineralization, osteogenic markers and viability of quiet equal concentrations of SV were investigated upon cells particularly of rodent origin [21][22][23][24][25][26][32][33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The examined cells were adipose tissue cells [ 13 , 14 ], myeloma cells [ 15 ], osteoblasts [ 16 18 ], alveolar fibroblasts [ 19 ] and bone marrow cells [ 20 ]. Pleiotropic effects have been reported like increased osteoblastic differentiation [ 20 22 ], promotion of the viability and proliferation of osteoblasts [ 16 , 23 ] and improvement of the mineralization [ 17 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies describing the application of simvastatin for the formation of bone in different bone defects have been encouraging and its effects on bone metabolism may have a great potential in medicine and dentistry 13,17,21 . In the present study, simvastatin was applied with two distinct carriers in criticalsized calvarial defects and its impact on new bone formation was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Asai et al approved in his study that application of SIM topically caused accelerated diabetic wound healing via promotion of angiogenesis and lymphangiogenesis . A preformulation study was made to check the capability of SIM to be adminstrated in the form of transdermal drug delivery system (TDDS) in controlled release manar using polymer like HPMC and Carbopol, to increase its bioavalability and decrease the dosing frequency; and the results showed that SIM can be suitable candidate for TDDS [44,45].…”
Section: Review Of Sim Different Medical Usesmentioning
confidence: 99%